Fracture Risk in Dialysis and Kidney Transplanted Patients: A Systematic Review. (5th July 2018) - Sidibé, Aboubacar; Auguste, David; Desbiens, Louis‐Charles; Fortier, Catherine; Wang, Yue Pei; Jean, Sonia; Moore, Lynne; Mac‐Way, Fabrice
ABSTRACT: Chronic kidney disease is associated with an increased risk of fracture and cardiovascular mortality. The risk of fracture in hemodialysis (HD), peritoneal dialysis (PD) and kidney transplant (KT) patients is higher when compared with the general population. However, there exists a knowledge gap concerning which group has the highest risk of fracture. We aimed to compare the risk of fracture in HD, PD, and KT populations. We conducted a systematic review of observational studies evaluating the risk of fracture in HD, PD, or KT patients. Eligible studies were searched using MEDLINE, Embase, Web of Science, and Cochrane Library from their inception to January 2016, and in grey literature. Incidences (cumulative and rate) of fracture were described together using the median, according to fracture sites, the data source (administrative database or cohort and clinical registry), and fracture diagnosis method. Prevalence estimates were described separately. We included 47 studies evaluating the risk of fracture in HD, PD, and KT populations. In administrative database studies, incidence of hip fracture in HD (median 11.45 per 1000 person‐years [p‐y]), range: 9.3 to 13.6 was higher than in KT (median 2.6 per 1000 p‐y; range 1.5 to 3.8) or in PD (median 5.2 per 1000 p‐y; range 4.1 to 6.3). In dialysis (HD+PD), three studies reported a higher incidence of hip fracture than in KT. Prevalent vertebral fracture (assessed by X‐rays or questionnaire) reported in HD was in a similar range as that reported in KT. Incidence of overall fracture was similar in HD and KT, from administrative databases studies, but lower in HD compared with KT, from cohorts or clinical registry studies. This systematic review suggests an important difference in fracture risk between HD, PD, and KT population, which vary according to the diagnosis method for fracture identification. © 2018 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.